2006
DOI: 10.1182/blood-2005-09-3605
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic correction of von Willebrand disease type 3 blood-derived endothelial cells with lentiviral vectors expressing von Willebrand factor

Abstract: Von Willebrand disease (VWD) is an inherited bleeding disorder, caused by quantitative (type 1 and 3) or qualitative (type 2) defects in von Willebrand factor (VWF). Gene therapy is an appealing strategy for treatment of VWD because it is caused by a single gene defect and because VWF is secreted into the circulation, obviating the need for targeting specific organs or tissues. However, development of gene therapy for VWD has been hampered by the considerable length of the VWF cDNA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 40 publications
0
43
0
1
Order By: Relevance
“…One approach may be to co-transduce BOECs with VWF. De Meyer et al 44 have recently demonstrated that WPB formation in VWD type 3 BOECs is restored upon lentiviral transduction with VWF. Another potential approach may be to overexpress the transcription factor KLF2 which has recently been shown to increase the average number of WPBs in HUVEC.…”
Section: Discussionmentioning
confidence: 99%
“…One approach may be to co-transduce BOECs with VWF. De Meyer et al 44 have recently demonstrated that WPB formation in VWD type 3 BOECs is restored upon lentiviral transduction with VWF. Another potential approach may be to overexpress the transcription factor KLF2 which has recently been shown to increase the average number of WPBs in HUVEC.…”
Section: Discussionmentioning
confidence: 99%
“…Blood outgrowth endothelial cells (BOECs) were isolated from the blood of healthy volunteers, characterized by immunofluorescent staining and grown in EBM-2/EGM-2 medium (Lonza, San Diego, CA) as described (34,35).…”
Section: Endothelial Cell Culturementioning
confidence: 99%
“…This distinctive feature paves the way toward many applications for which γ-RVs are not suitable. Moreover, LV can accommodate larger transgenes [up to ~10 kilobases (kb)] compared to when γ-RVs are used though vector titers tend to decrease with larger inserts [14,24,25]. It is critically important to ensure that the LVs are replication-defective because HIV-1 is a human pathogen.…”
Section: Lentiviral Vectorsmentioning
confidence: 99%